Comparison of the Quality of Life Using the Human Development Index Based on the Global Supply Chain - Askar Nailevich Mustafin; Nataliya Sergeevna Seliverstova; Jaroslav Gonos; Viera Ivankova (International Journal of Supply Chain Management, 2019)
Quality of life and methods of its measurement are topics that are quickly becoming the subject of both professional and social discussions based on the global supply chain. The basic idea of this article is to compare the quality of life in the Russian Federation and Germany. These are powerful economies that offer an interesting confrontation. We also contribute to this comparison using Slovakia as an example of the confrontation of large and economically strong countries with a small country. The main indicator for expressing the quality of human life in the article is the Human Development Index (HDI), based on which we used a comparative analysis. The first part of the article provides a theoretical framework and characteristics of indicators. In the second part of the article, we analyzed the 10-year development of the selected countries' indicators. The results show a positive trend in the growth of quality of life, where Germany is clearly the leader among the selected countries, and we can state the gradual slow convergence of the Russian and Slovak economy to the German one.